The capability of Motorways of the Sea of being competitive against road transport. The case of the Italian mainland and Sicily. (January 2017) - Lupi, Marino; Farina, Alessandro; Orsi, Denise; Pratelli, Antonio
Abstract: The paper deals with a quantitative analysis on the competitiveness of intermodal transport, based on Motorways of the Sea (MoS), in comparison with all-road transport. This analysis is applied to MoS routes connecting the Italian mainland with Sicily. The study involves: a detailed intermodal network model which compares monetary costs and travel times from all relevant origins in the mainland to all relevant destinations in Sicily; and a survey carried out at some representative trucking firms operating to/from Sicily. The aim of the interviews has been: on one side to make a comparison between the theoretical and actual mode of transport and routes taken, and in case they are different, to understand the reasons of the discrepancy; on the other side to determine what are the main aspects taken into account by trucking companies in their modal choice, in order to understand how the competiveness of MoS against road transport can be improved. The results of the analysis show that the modal choice is affected by several elements: monetary costs and travel times; reliability of MoS routes; availability of MoS routes; MoS routes frequencies; but it resulted from the interviews that monetary costs and travel times are the most important factors considered by trucking companies in the modal and route choice. This study has also shown that an improvement of MoS routes on the Italian Adriatic side is necessary: actually, a strong reason for which in Italy MoS traffic is still a small percentage of road traffic is the low number of MoS routes currently in operation and their low frequency. This analysis could help decision makers, and maritime operators, to efficiently invest in the improvement of MoS routes. Moreover, this analysis, developed for an Italian case study, can be applied to other European and Mediterranean scenarios. Highlights: A detailed model allows to compare costs and times of all-road and MoS transport. The main factors affecting mode choice are analyzed trough a survey at trucking firms. Modal choice is affected in particular by monetary costs and travel times. MoS traffic is a small percentage of road traffic because of the low number of routes. The analysis, developed for an Italian case study, can be applied to other European scenarios.